Genetic characterisation of 13 rapidly mutating Y-STR loci in 100 father and son pairs from South and East Turkey - Ay, Mustafa; Serin, Ayse; Sevay, Huseyin; Gurkan, Cemal; Canan, Husniye (Taylor & Francis Ltd, 2018)
Background: Rapidly mutating (RM) Y-STRs recently emerged as a useful genotyping tool that can counteract problems normally associated with traditional Y-STRs. For instance, RM Y-STRs have the potential to differentiate Y-chromosomes from both close and distant paternal relatives. Aim: Characterisation of 13 RM Y-STR loci in a new sample pool from Turkey in terms of population genetic data and mutation rates. Subjects and methods: One hundred father-son pairs from South and East Turkey were genotyped. Based on the 99 father haplotypes unique to the current study, statistical parameters of forensic interest were computed. Nei's D-A distances among 112 global population datasets were estimated and visualised by phylogenetic and multidimensional scaling (MDS) analyses. Results: Fifteen father-son pairs were found to differ at a single locus and four at two loci, resulting in a differentiation rate of 19%. Mutations were observed at 10 out of 13 loci, with rates ranging from 1 x 10(-2) to 6 x 10(-2). Conclusion: Mutation rates and differentiation rates between the father-son pairs were similar to those from the literature. In contrast to previous work, novel phylogenetic tree construction results based on Nei's D-A distances suggested a close correlation between the geographic and genetic distances observed, except for known cases of past mass migration events.
Keywords: RM Y-STRs; father-son pairs; mutation rates; genetic-geographic structuring